ANTARA HUKUM DAN KEKERASAN: EVALUASI EFEKTIVITAS HUKUM HUMANITER INTERNASIONAL DALAM MELINDUNGI SIPIL PALESTINA - Davy Darma Putra; Arif Rahman, Tarsisius Susilo, Agustinus Adi Santoso, Muhammad Taufik Zega (JOURNAL OF LAW AND NATION, 2025)
The prolonged conflict between Israel and Palestine has become one of the most complex testing grounds for the application of International Humanitarian Law (IHL), particularly in terms of the protection of civilians. The purpose of this study is to evaluate the effectiveness of IHL implementation in the context of this conflict, as well as to identify factors that contribute to violations of the law, impunity, and weak protection for Palestinian civilians. This study also aims to describe how international institutions respond to these violations and the extent to which these responses are able to meet the basic principles of humanitarian law. This study uses a descriptive qualitative approach with methods of literature review and analysis of international legal documents, reports from humanitarian organisations, UN resolutions, and field data from independent institutions such as Human Rights Watch and the ICRC. The data is analysed using a normative and empirical approach to evaluate the compatibility between legal norms and their implementation in the field. Key findings show that although the humanitarian legal framework clearly regulates the protection of civilians, the reality shows systematic violations of the principles of distinction, proportionality, and precaution by both sides, with the greatest impact felt by Palestinian civilians. In addition, this study found that international institutions are often unable to take effective action due to global political pressure and the use of veto power in the UN Security Council. Power imbalances and media dominance further exacerbate bias in law enforcement. The conclusion of this study confirms that the existence of IHL, despite its strong normative basis, remains very weak in its implementation if not accompanied by independent enforcement mechanisms that are free from political interests. Therefore, reforms are needed in the structure of international law enforcement, strengthening the role of civil society, and public education on the principles of humanitarian law to create more equitable and effective civilian protection in modern armed conflicts.